Updated WHO nomenclature of head and neck lesions and associated imaging findings - Nisa Oren; Anatoliy Vaysberg; Daniel T. Ginat (Insights into Imaging, 2019)
Abstract This article reviews the imaging features of head and neck lesions with updated 2017 World Health Organization (WHO) nomenclature. The major WHO changes include refined terminology of existing entities, descriptions of new tumor types, elimination of defunct categories, and updated biological characterization of various tumor types. In particular, the updates pertaining to the following conditions will be reviewed: tumors of the oral cavity and oropharynx, including HPV-positive or HPV-negative squamous cell carcinoma, small cell carcinoma; tumors of the hypopharynx, larynx, trachea, and parapharyngeal space, including nomenclature revisions for laryngeal neuroendocrine tumors; tumors of the nasal cavity and paranasal sinuses including newly added entities such as NUT carcinoma and biphenotypic sinonasal sarcoma; odontogenic and maxillofacial bone tumors, including the reversal of terminology for certain cystic lesions; tumors of the salivary glands, including updated terminology related to high-grade transformation and polymorphous adenocarcinomas tumors; temporal bone lesions including modifications of the nomenclature and classification criteria; tumor-like lesions of the neck and lymph nodes, with a discussion encompassing developmental cysts, metastases of unknown primary, and heterotopia-associated neoplasia; and mucosal melanoma. Familiarity with the proper WHO terminology for conditions that might be mentioned in differential diagnoses and a general understanding of the behavior of head and neck lesions can help optimize imaging assessment and reporting.